Safety Management Practices in Small and Medium Enterprises in India - Seema Unnikrishnan; Rauf Iqbal; Anju Singh; Indrayani M. Nimkar (Elsevier, 2015)
Background: Small and medium enterprises (SMEs) are often the main pillar of an economy. Minor accidents, ergonomics problems, old and outdated machinery, and lack of awareness have created a need for implementation of safety practices in SMEs. Implementation of healthy working conditions creates positive impacts on economic and social development. Methods: In this study, a questionnaire was developed and administered to 30 randomly chosen SMEs in and around Mumbai, Maharashtra, and other states in India to evaluate safety practices implemented in their facilities. The study also looked into the barriers and drivers for technology innovation and suggestions were also received from the respondent SMEs for best practices on safety issues. Results: In some SMEs, risks associated with safety issues were increased whereas risks were decreased in others. Safety management practices are inadequate in most SMEs. Market competitiveness, better efficiency, less risk, and stringent laws were found to be most significant drivers; and financial constraints, lack of awareness, resistance to change, and lack of training for employees were found to be main barriers. Conclusion: Competition between SMEs was found to be major reason for implementation of safety practices in the SMEs. The major contribution of the study has been awareness building on safety issues in the SMEs that participated in the project.